Students' Language Creativity in Creating English Poems: A Linguistic Perspective - Katili, Adriansyah Abu (Jambura Journal of English Teaching and Literature, 2023)
This article is aimed at discussing the language creativity of students of the English Department in creating English poems. The is article is based on the analysis of students who created English poems enrolling at the English Department of the State University of Gorontalo. The analysis was conducted from a linguistic perspective. The research has found that the students were creative in creating diction, repetition, and metaphor.